2019
DOI: 10.3390/nano9010116
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Self-Assembled Polydopamine-Modified Electrospun Fibers for Highly Effective Removal of Organic Dyes

Abstract: Polydopamine (PDA) nanoparticles can be used as an adsorbent with excellent adsorption capacity. However, nanosized adsorbents are prone to aggregation and thus are severely limited in the field of adsorption. In order to solve this problem, we utilized polydopamine in-situ oxidation self-polymerization on the surface of polycaprolactone (PCL)/polyethylene oxide (PEO) electrospun fiber after solvent vapor annealing (SVA) treatment, and successfully designed and prepared a PCL/PEO@PDA composite membrane. The SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…where Q is the flow rate (m 3 /h) and T is the time (h). Combining Equations (16) and (17) results in:…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…where Q is the flow rate (m 3 /h) and T is the time (h). Combining Equations (16) and (17) results in:…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic constant k of the above catalytic reduction reaction was calculated to be 0.16597s −1 and 0.00401 s −1 , respectively. The kinetic constant k could intuitively reflect the speed of the catalytic reduction reaction [58][59][60][61][62][63][64][65]. Obviously, PEI/PCL@PdNPs catalytically reduced 4-NP faster.…”
Section: Catalytic Performance Of Pei/pcl@pdnps Compositesmentioning
confidence: 99%
“…Thus, present obtained composite hydrogels demonstrated a new clue for the design of self-assembled nanomaterials and organized composites. [54][55][56][57][58][59][60][61][62][63][64][65]…”
Section: Preparation and Catalytic Performance Of The Aunp/t-g Hydrogelmentioning
confidence: 99%